Health and production assessment of rainbow trout and socioeconomic factors of producers in authorized production centers in apurímac: analysis of key factors and mortality - Zarate, Ivar; Sanchez, Cristian Zoilo; Cayllahua, Paul Anthony; Meléndez, Keyro Alberto (Revista de Ciências Agroveterinárias, 2025)
The research evaluates the sanitary and productive factors in rainbow trout farming centers in Apurímac, Peru, identifying challenges related to infrastructure, sanitary management, and productive practices that affect the sector's sustainability. The centers use systems such as concrete ponds and floating cages but show inconsistencies in monitoring critical parameters, such as pH (70%) and stocking density (76.7%), while disinfection practices (93.3%), pest control (46.7%), and dead animal disposal lack standardization, increasing sanitary risks. Regarding feeding, 96.7% of producers use commercial balanced feeds, although deficiencies persist in feed conversion ratio calculation (80%), impacting efficiency. Mortality rates, higher in early stages and during the rainy season, reach up to 40% in fry and 20% in juveniles, associated with water quality, fry origin, and environmental management. Through statistical analyses, the study highlights the importance of implementing standardized sanitary protocols and strengthening technical training for producers to reduce mortality and optimize production. Additionally, improving infrastructure, as 30% of centers use materials like adobe, and environmental management is recommended to mitigate risks associated with diseases and climatic fluctuations. The study underscores the need for integrated policies that promote sustainable practices, reduce environmental impact, and enhance sector competitiveness, ensuring its contribution to food security and economic development in vulnerable rural communities. These findings provide a foundation for implementing strategies to increase productive efficiency and guarantee more equitable and sustainable aquaculture development in the region.